A survey of salaries and position classification of school librarians in private sectarian schools in Metro Manila - Enciso, Clarita Arcangel (1991)
This study attempts to find out the salaries and position classification of school librarians. It seeks to gather further empirical data about the salaries, monetary and other benefits received. It was conducted among sixty-nine of 106 schools librarians in 105 sectarian private schools in Metro Manila.